Equivalent Clinical Outcomes Following Favored Treatments of Chronic Scapholunate Ligament Tear. Issue 2 (July 2017) - Wang, Pengcheng; Stepan, Jeffrey G.; An, Tonya; Osei, Daniel A.
Background: Optimal treatment of chronic scapholunate (SL) instability remains controversial. Many surgical techniques have been proposed with varied results in subsequent case series; however, there is limited evidence demonstrating the relative effectiveness of the different treatment options. Questions/Purposes: We conducted a systematic review of the English literature to compare outcomes from capsulodesis and ligament reconstruction for treatment of chronic scapholunate instability. Methods: An electronic database search using keywords associated with scapholunate ligament instability was performed. A total of 511 studies were identified. All studies with scapholunate ligament tears >4 weeks after the initial injury were included in the review. Data extracted included patient demographics, wrist range of motion, and radiographic outcome measures. Results: A total of 308 patients from 11 studies met the inclusion criteria and were included in the study. The average time to surgery from initial injury was 11 months. There was no significant difference in wrist flexion or extension after capsulodesis or reconstruction. The weighted mean for postoperative wrist extension/flexion was 56°/45.6° in the capsulodesis group and 40.9°/47.3° in the reconstruction group. Pooled means of SL angle and SL gap were 60.3° and 3.44 mm after capsulodesis and 56.5 and 2.72 mm after reconstruction, respectively. Conclusions: This systematic review failed to demonstrate any significant difference in outcomes from capsulodesis or reconstruction for treatment of chronic scapholunate instability. However, the retrospective studies examined were notably heterogeneous in design with high estimates of variance. Further prospective trials are necessary to determine an ideal treatment strategy.